(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
From ancient times to the present, various civilizations and cultures have existed in the territory of Central Asia. In this article, we have thoroughly analyzed the early medieval numismatic materials of the Ferghana Valley region, one of the oldest regions of Central Asia, compared the coins found during excavations in archaeological monuments, and made general conclusions. O.I.Smirnova, L.S.Baratova, E.Rtveladze, G.Babayarov carried out extensive works on the numismatics of this region, and we analyzed the data in their scientific works. We can say that the coins found in Fergana region, like the coins found in other historical regions of our country, give us very clear and important information about the period of their minting